The Macroeconomics Shocks and the Brazilian Agricultural Price Evolution - A VAR Analysis Approach - Humberto Spolador; Geraldo Barros; Mirian Bacchi (European Regional Science Association (ERSA), 2011)
The findings presented in this paper come from our study of the effects of Brazilian macroeconomic policy on the Brazilian Farm [product] Price Index using an adapted version of Frankel's (1986 & 2006) theoretical model. The study examined the connection between Brazilian farm prices and external variables (worldwide importation of agribusiness products, international commodity prices, and foreign real interest rates) and between Brazilian farm prices and domestic variables (GDP, the real exchange rate, and local interest rates).
Keywords: 330